THERAPEUTIC PLASMA EXCHANGE IN THREE SCENARIOS COMPLICATING HYPERTHYROIDISM: A RETROSPECTIVE CASE SERIES - Anuar, MZ Azim; Katiman, Elliyyin; Aziz, Hazwani; Mazlan, Sadanah Aqashiah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Therapeutic plasma exchange (TPE) represents a viable option for managing thyroid storms when conventional therapies prove inadequate. Despite its utility, the precise indications for TPE have not been well established. Herein, we present our experience with three cases, elucidating treatment responses through changes in free T4 levels, which ultimately facilitated rapid clinical improvement. We describe the clinical presentations and laboratory profiles of three young patients (aged 17-27 years) admitted to Hospital Kajang for hyperthyroidism. CASE 1 A 17-year-old female, presented with a severe thyroid storm complicated by hepatic encephalopathy and cardiomyopathy requiring mechanical ventilation. On day 3, TPE was initiated along with conventional therapy, which resulted in a 78% reduction in free T4 levels by day 4, with subsequent recovery by day 6. CASE 2 A 27-year-old female with carbimazole-induced agranulocytosis and had an inadequate response to secondline antithyroid drugs, underwent four cycles of TPE as preoperative optimization for total thyroidectomy, achieving a 43% reduction in free T4 levels within 5 days, facilitating a successful surgical outcome. CASE 3 An 18-year-old male, following a trivial fall resulting in a left femoral neck fracture, developed a severe thyroid storm. The urgency for joint surgery prompted four cycles of plasmapheresis, culminating in a 54% reduction in free T4 levels within 3 days, allowing for successful surgery by day 8. All patients were discharged well without complications. CONCLUSION The action of TPE results primarily from plasma removal of cytokines, circulating autoantibodies, thyroid hormones, and their bound proteins. Our cases underscore the potential efficacy of plasmapheresis in hyperthyroidism management. They exemplify its effectiveness in diverse scenarios: managing severe, complicated thyroid storm; bridging to total thyroidectomy in carbimazole-induced agranulocytosis and failing conventional therapy; and urgently ameliorating thyroid storm before a jointpreserving procedure for a femoral neck fracture.